SISTEM PAKAR PENENTUAN MENU MAKANAN SEHAT PENDERITA DIABETES MELITUS BERBASIS MOBILE - Candra, Suriyanti (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2014)
Healthy diet for diabetics is important to help people in controlling their blood sugar levels. Diabetic diet meal plans assisted by nutritionists. Nutritionists will adjust diet with caloric needs, schedule and type of food eaten in accordance with the conditions of diabetics. This research aims to produce expert systems that help diabetics prepare their own food menu based on knowledge that has been acquired from a nutritionist, so diabetics can save time and cost consultancy. Expert system that constructed based on mobile and especially for devices with android platform. Based on compatibility testing results show that the expert system can run on a variety of types and brands of android device. Based on the percentage of testing aspects of software engineering, respondents gave a good response at 52,2%, testing the functionality aspect, respondents gave a good response at 60,0% and testing aspects of visual communication, respondents gave a good response at 58,1%. The results showed that it has managed to produce an expert system that could assist the user in setting a good diet and healthy for users. Because the result of this research is at precisely scores 2160-2700 on 2265 scores were obtained by calculating the Likert’s Summated Rating (LSR)  method, which means the results of the questionnaire respondents indicating the application is positive and considered as successful.